AlloDerm with Split‐Thickness Skin Graft for Coverage of the Forearm Free Flap Donor Site. (22nd November 2013) - Wester, Jacob L.; Pittman, Amy L.; Lindau, Robert H.; Wax, Mark K.
Abstract : Objective: Major causes of donor site morbidity after free flap harvest are lack of split‐thickness skin graft (STSG) take and tendon exposure. Long‐term cosmesis remains poor. AlloDerm has shown cosmetically better donor site healing, albeit prolonged healing. We sought to evaluate the use of STSG with AlloDerm compared with STSG alone. Study Design: Case series with chart review. Setting: Academic tertiary care medical center. Methods and Subjects: Institutional review board–approved study. Microvascular database queried from 2002 to 2012. Subjects with forearm free flaps and either AlloDerm + STSG or STSG alone for donor site reconstruction were included. Morbidity outcomes were compared. Results: Eighty patients (50 male, 30 female) received AlloDerm + STSG at the donor site. Major and minor donor site complications were 15.0% and 18.8% in the AlloDerm + STSG group compared with 10.2% and 16.9% in the STSG‐only group ( P =. 30 and P =. 72), respectively. Complete STSG loss (5.0% vs 3.0%, P =. 48), tendon exposure (5.0% vs 5.4%, P = 1.0), functional impairment (2.5% vs 1.8%, P =. 66), infection (8.8% vs 9.6%, P = 1.0), hematoma/seroma (5.0% vs 3.6%, P =. 73), and paresthesia (1.3% vs 3.6%, P =. 43) were not significant. No patients required a second STSG after loss in the AlloDerm + STSG group compared with 60% ( P =. 17). Cosmetic results were superior in the AlloDerm + STSG group as rated by the surgeon (3.5 vs 2.6, P =. 03) and patients (3.7 vs 2.9, P =. 05) on a scale of 1 to 5. Conclusion: Our results suggest that the use of AlloDerm with STSG can provide thicker coverage of the forearm defect, with minimal donor site morbidity and superior cosmetic results compared with STSG alone.